Impact of milk protein type on the viability and storage stability of microencapsulated Lactobacillus acidophilus using spray drying - Soukoulis, Christos; Behboudi-Jobbehdar, Solmaz; Yonekura, Lina; Parmenter, C.D.J.; Fisk, Ian D. (Springer Verlag, 2014)
Three different milk proteins — skim milk powder (SMP), sodium caseinate (SC) and whey protein concentrate (WPC) — were tested for their ability to stabilize microencapsulated L. acidophilus produced using spray drying. Maltodextrin (MD) was used as the primary wall material in all samples, milk protein as the secondary wall material (7:3 MD/milk protein ratio) and the simple sugars, d-glucose and trehalose were used as tertiary wall materials (8:2:2 MD/protein/sugar ratio) combinations of all wall materials were tested for their ability to enhance the microbial and techno-functional stability of microencapsulated powders. Of the optional secondary wall materials, WPC improved L. acidophilus viability, up to 70 % during drying; SMP enhanced stability by up to 59 % and SC up to 6 %. Lactose and whey protein content enhanced thermoprotection; this is possibly due to their ability to depress the glass transition and melting temperatures and to release antioxidants. The resultant L. acidophilus powders were stored for 90 days at 4 °C, 25 °C and 35 °C and the loss of viability calculated. The highest survival rates were obtained at 4 °C, inactivation rates for storage were dependent on the carrier wall material and the SMP/d-glucose powders had the lowest inactivation rates (0.013 day−1) whilst the highest was observed for the control containing only MD (0.041 day−1) and the SC-based system (0.030 day−1). Further increase in storage temperature (25 °C and 35 °C) was accompanied by increase of the inactivation rates of L. acidophilus that followed Arrhenius kinetics. In general, SMP-based formulations exhibited the highest temperature dependency whilst WPC the lowest. d-Glucose addition improved the storage stability of the probiotic powders although it was accompanied by an increase of the residual moisture, water activity and hygroscopicity, and a reduction of the glass transition temperature in the tested systems.